Toward a womanist ethic of incarnation : Black bodies, the Black church, and the Council of Chalcedon - Turman, Eboni Marshall (Black religion, womanist thought, social justice., 2013)
The Black Church is an institution that emerged in rebellion against injustice perpetrated upon black bodies. How is it, then, that black women's oppression persists in black churches that espouse theological and ethical commitments to justice? The book engages the Chalcedonian Definition as the starting point for exploring the body as a moral dilemma. It reveals how the body of Christ has historically posed a problem for the church, and has produced a Christian trajectory of violence that has resulted in the breaking of the body of Christ. A survey of the black body as an American problem provides the lens for understanding how the theological problem of body has functioned as a social dilemma for black people. An exploration of the black Social Gospel as the primary theological trajectory that has approached the problem of embodied difference reveals how body injustice, namely sexism, functions behind the veil of race in black churches.